Sulfonated polytriazoles from a new fluorinated diazide monomer and investigation of their proton exchange properties - Singh, Asheesh; Mukherjee, Rajdeep; Banerjee, Susanta; Komber, Hartmut; Voit, Brigitte (Journal of Membrane Science, 2014)
A series of new fluorinated sulfonated polytriazoles with varying degree of sulfonation was synthesized using the click reaction of a new diazide monomer; 4,4-bis[3-trifluoromethyl-4(4-azidophenoxy)phenyl]biphenyl (QAZ) and 4,4'-diazido-2,2'-stilbenedisulfonic acid disodium salt (DADSDB) with 4,4'-(propane-2,2-diyl)bis((prop-2-ynyloxy)benzene) (BPEBPA). The structures of the polytriazoles were confirmed by FTIR and NMR (1H, 13C and 19F) spectroscopy. The polytriazoles exhibit high molecular weights, and good solubility and film forming capabilities, combined with high thermal and chemical stabilities, low water uptake, good dimensional stability and high mechanical properties which makes them interesting materials as proton exchange membranes. TEM images of the polytriazole membranes showed nano-phase separated morphology with ionic clusters in the range of 5-65nm. The proton conductivities of the fluorinated membranes were found in the range of 12-76mS/cm at 80°C in water. A maximum value of even 112mS/cm was achieved for the non-fluorinated sample. © 2014 Elsevier B.V.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Click polymerization; Fluorinated sulfonated polytriazoles; Membrane properties; NMR study